Kekambuhan gingivitis hiperplasi setelah gingivektomi (Recurrent of hyperplastic gingivitis after gingivectomy) - Iwan Ruhadi; Izzatul Aini (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
The inflammatory enlargement is clinically called hyperthropic gingivitis or gingival hyperplasia and generally related to local or systemic factors. They could be edematous or fibrous. The former is treated by scaling, but the latter that could not be treated by scaling only has to be removed by gingivectomy. There are some cases of gingivectomy resulting in recurrences. The writer wanted to find out the cause of the recurrences. The types of research were clinical and laboratories observational studies. The criteria of sample were: male or female patient who came to periodontal clinic of Faculty of Dentistry Airlangga University. They were diagnosed gingivitis hyperplasia; had no systemic diseases; did not wear the orthodontic appliances, prosthesis, and crown and bridge; do not smoke. The indicated teeth to be observed were the labial side of maxillary front teeth. The teeth had score hyperplastic index (HI) = 2 at the 2nd weeks after scaling. There were 7 samples taken selectively. The results of the studies were based on the comparison of 1) hyperplasia index (HI); 2) the number and percentage of monosite and leucocytes from white blood impedance coutl (WIC) and white blood optical coutl (WOC); 3) plaque Index; and 4) gingival index. The result of gingivectomy was reevaluated on the 30th, 45th, 60th, 90th day. The research concluded that the number of monosite was normal, but the dental plaque still accumulated and eventually caused the recurrences of the inflammation.